Towards the investigation on the effect of the forearm rotation on the wrist FMG signal pattern using a high-density FMG sensing matrix. Issue 1 (1st January 2020) - Xiao, Zhen G.; Menon, Carlo
Abstract: Force myography (FMG) is an emerging technique to predict extremity movement. The FMG signals captured near the wrist can be used to predict many hand gestures. However, the wrist FMG pattern of a gesture changes along with different forearm positions. It is difficult to accurately predict a gesture without knowing the effect of the forearm position on the wrist FMG pattern. To investigate such an effect, we developed a novel setup to register the pattern using the off-the-shelf force-sensing matrix to capture the change of the pattern during forearm rotation for two distinct hand gestures. Based on the collected data, we observed the wrist FMG patterns shifted in relation to the forearm orientation in some scenarios. We analyzed the results and examined the viability to use such a setup to facilitate future studies.